Unity artificial intelligence programming : add powerful, believable, and fun AI entities in your game with the power of Unity 2018! /: add powerful, believable, and fun AI entities in your game with the power of Unity 2018!. (2018) - Aversa, Davide; Kyaw, Aung Sithu; Peters, Clifford
No abstract available